Human Relations untuk Menjaga Dedikasi Relawan Mafindo Cegah Kejahatan Siber - Mochammad Helmy Fikri; Niken Puspitasari (Universitas Prof. Dr. Moestopo (Beragama), 2026)
The presence of Mafindo volunteers is important to reduce the level of cyber crime in Indonesia. Polri data shows that in 2022, the cyber crime increased 14 times compared to 2021.Mafindo volunteers come from different cultural backgrounds, which may experience obstacles in building harmonious relationships within the organization. These differences can cause stereotypical misunderstandings and conflicts between individuals, which ultimately reduce the enthusiasm of volunteers in guarding cybercrime. The research results show that to avoid conflict and maintain the enthusiasm of volunteers, Mafindo management approaches human relations with three approaches, namely, 1). OPSDM as a center for human relations activities, with activities in the form of: Caring to volunteers' emotions, a place to convey complaints, giving appreciation, and increasing volunteer capacity, 2). Implementation of an egalitarian system in organizations, 3). Collegial-collective decision-making culture. These three findings show that relationships between people are a central factor in the progress of harmonization in an agency/organization.